THE HIJRAH PHENOMENON AS A SOCIAL IDENTITY AMONG MUSLIM MILLENNIALS IN INDONESIA - Mohammad Izdiyan Muttaqin; Abdullahi Ahmed An-Na'im (Karimiyah: Journal of Islamic Literature and Muslim Society, 2026)
The hijrah phenomenon a contemporary Islamic revivalist movement signifying a personal and communal turn toward more devout Muslim practice has emerged as one of the most salient socioreligious dynamics shaping the identity landscape of Indonesian Muslim millennials in the post-Suharto era. This article examines how hijrah functions not merely as a spiritual transformation but as a complex social identity marker that intersects with digital media consumption, peer-group dynamics, market forces, and broader socio-political configurations in contemporary Indonesia. Drawing on an integrative review of empirical studies published between 2019 and , this article synthesises findings from multiple urban and semi-urban contexts across the archipelago, including Jakarta, Bandung, Yogyakarta, Medan, Aceh, and Lombok. Theoretically anchored in Social Identity Theory (Tajfel & Turner), the sociology of religion (Giddens’ reflexive modernity), and the concept of “popular piety,” the article argues that hijrah constitutes a multi-layered identity project in which millennials negotiate selfhood between religious authenticity, digital performativity, and consumer culture. The article further explores how Islamic influencers, da’wah communities, and social media ecosystems serve as key agents in the production and circulation of hijrah as a social identity. It concludes by reflecting on the tensions inherent in the commercialisation of hijrah, the risk of superficial religiosity, and the potential of the movement to serve as a vehicle for genuine moral and civic transformation.